Study on antioxidant capacity, antibacterial activity, phenolic profile and microbial screening of selected malaysian and turkish honey / Mohd Izwan Zainol - Mohd Izwan, Zainol (2016)
Honey has been implicated in promoting healing process of superficial wounds like burn injury and decubitus ulcer. It is attributed to high antioxidant and antibacterial activities through prevention of bacterial infection. Phytochemical contents, hydrogen peroxide, low pH and high osmolarity are the key factors that affect honey bioactivity. These properties are unique to different honey type depending mainly on their geographical origin, bee species, and floral source. Influence of these variations to honey production has drawn questions to the level of bioactivity between honey, especially from the different geographical location. To date, there are very limited data on Malaysian and Turkish honey bioactivities to answer such questions. Therefore, the present study aims to investigate the antioxidant and antibacterial activities of five Malaysian honey and five Turkish honey. The antioxidant activity of honey was evaluated using spectrophotometric measurements including 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2‘-azino-bis(3-ethylbenzothiazoline-6-sulphuric acid) (ABTS) and Ferric Reducing Antioxidant Power (FRAP) assays. Total phenolic content (TPC) and Liquid Chromatography-Mass spectrophotometry (LC-MS) were employed to characterize the phenolic profile of honey samples. Antibacterial properties of honey were evaluated via Minimum Inhibitory Concentration (MIC)/Minimum Bactericidal Concentration (MBC) assays and agar well diffusion assay against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Bacillus cereus. 16S rDNA gene sequencing analysis was conducted for pathogenic bacterial screening. Kelulut honey possessed the highest antioxidant activity with the scavenging ability of 0.00421±0.03μeq AAE/mg and FRAP value of 13.37±0.49μMx100/mg. Gelam honey, however, detected highest in ABTS assay with 93.74% inhibition while 2.216±0.02μg GAE/mg in TPC. LC-MS detected six phenolic acids in honey tested which present in various combination of; 2,3-dihydroxybenzoic acid, caffeic acid, gallic acid, p-salicylic v acid, syringic acid and vanillic acid. Gelam honey exerted highest antibacterial activity against S. aureus with 5% MIC and 6.35% MBC, E. coli with 12.5% MIC and 15% MBC and against P. aeruginosa with 10% MIC and 12.5% MBC. B cereus however only inhibited by gelam, tualang, carob blossom and spring honey at 15% while killed at 20% by those honey. Kelulut honey gave equal effects on all bacteria tested for both MIC and MBC assays (20%). In diffusion assay, the highest antibacterial activity was demonstrated by spring honey against B. cereus with 28.54 EPC of total activity while 27.72 EPC of non-peroxide activity. Two honey failed to inhibit bacterial growth neither for total activity nor non-peroxide activity, namely lavender honey against E. coli and P. aeruginosa and pine honey against E. coli. Significant differences were found between total and non-peroxide activities of acacia honey against B. cereus, lavender and wildflowers honey against S. aureus as well as wildflowers and carob blossom honey against E. coli and B. cereus. Sixty-one Gram-positive bacilli were isolated from tested honey with the dominance of Bacillus pumilus (40.90%). In conclusion, Gelam and kelulut honey from Malaysia and spring honey from Turkey possessed excellent antioxidant capacities and antibacterial properties against bacterial species, especially Gram-positive ones. It was likely due to variation in their physicochemical properties that influence by their floral source, place of origin as well as their bee species.